Demontagefreie und schonende mechanische Reinigung industrieller Wärmeübertrager und Kühlkreisläufe. Issue 6 (30th March 2018) - Kuschnerow, Jan; Klein, Norbert; Schlüter, Florian; Augustin, Wolfgang; Scholl, Stephan; Strathmann, Martin; Schaule, Gabriela; Hammann, Hans‐Gerd
Abstract: The COMPREX®‐process is an in place cleaning process for pipelines and heat exchangers. It is based on a laminar flow of water and superimposed pulses of compressed air. The process does neither need chemical cleaning agents nor the dismantling of the plant. It is a material friendly process, even towards ageing equipment. Mobile cleaning units enables the application of this process at the applier's site. Furthermore, this process reduces the required time of shutdown. That makes frequent cleaning more economical so that ageing of deposits in the plant can be reduced.